Population Pharmacokinetic Study of Benznidazole in Pediatric Chagas Disease Suggests Efficacy despite Lower Plasma Concentrations than in Adults - Altcheh, Jaime Marcelo (2014)
Introduction:Chagas disease, caused by the parasite Trypanosoma cruzi, can lead to long term cardiac morbidity. Treatment of children with benznidazole is effective, but no pediatric pharmacokinetics data are available and clinical pharmacology information on the drug is scarce.Patients and Methods:Prospective population pharmacokinetic (PK) cohort study in children 2-12 years old with Chagas disease treated with oral benznidazole 5-8 mg/kg/day BID for 60 days. (clinicaltrials.gov #NCT00699387).Results:Forty children were enrolled in the study. Mean age was 7.3 years. A total of 117 samples were obtained from 38 patients for PK analysis. A one compartment model best fit the data. Weight-corrected clearance rate (CL/F) showed a good correlation with age, with younger patients having a significantly higher CL/F than older children and adults. Simulated median steady-state benznidazole concentrations, based on model parameters, were lower for children in our study than for adults and lowest for children under 7 years of age. Treatment was efficacious in the 37 patients who completed the treatment course, and well tolerated, with few, and mild, adverse drug reactions (ADRs).Discussion:Observed benznidazole plasma concentrations in children were markedly lower than those previously reported in adults (treated with comparable mg/kg doses), possibly due to a higher CL/F in smaller children. These lower blood concentrations were nevertheless associated to a high therapeutic response in our cohort. Unlike adults, children have few adverse reactions to the drug, suggesting that there may be a direct correlation between drug concentrations and incidence of ADRs. Our results suggest that studies with lower doses in adults may be warranted.Trial Registration:ClinicalTrails.gov NCT00699387.